Development of an optimised 1:1 physiotherapy intervention post first-time lumbar discectomy: a mixed-methods study. Issue 2 (25th February 2016) - Rushton, A; White, L; Heap, A; Calvert, M; Heneghan, N; Goodwin, P
Abstract : Objectives: To develop an optimised 1:1 physiotherapy intervention that reflects best practice, with flexibility to tailor management to individual patients, thereby ensuring patient-centred practice. Design: Mixed-methods combining evidence synthesis, expert review and focus groups. Setting: Secondary care involving 5 UK specialist spinal centres. Participants: A purposive panel of clinical experts from the 5 spinal centres, comprising spinal surgeons, inpatient and outpatient physiotherapists, provided expert review of the draft intervention. Purposive samples of patients (n=10) and physiotherapists (n=10) (inpatient/outpatient physiotherapists managing patients with lumbar discectomy) were invited to participate in the focus groups at 1 spinal centre. Methods: A draft intervention developed from 2 systematic reviews; a survey of current practice and research related to stratified care was circulated to the panel of clinical experts. Lead physiotherapists collaborated with physiotherapy and surgeon colleagues to provide feedback that informed the intervention presented at 2 focus groups investigating acceptability to patients and physiotherapists. The focus groups were facilitated by an experienced facilitator, recorded in written and tape-recorded forms by an observer. Tape recordings were transcribed verbatim. Data analysis, conducted by 2 independent researchers, employed an iterative and constant comparative process of (1) initial descriptive coding to identify categories and subsequent themes, and (2) deeper, interpretive coding and thematic analysis enabling concepts to emerge and overarching pattern codes to be identified. Results: The intervention reflected best available evidence and provided flexibility to ensure patient-centred care. The intervention comprised up to 8 sessions of 1:1 physiotherapy over 8 weeks, starting 4 weeks postsurgery. The intervention was acceptable to patients and physiotherapists. Conclusions: A rigorous process informed an optimised 1:1 physiotherapy intervention post-lumbar discectomy that reflects best practice. The developed intervention was agreed on by the 5 spinal centres for implementation in a randomised controlled trial to evaluate its effectiveness.